Morphology and Crystal Planes Effects on Supercapacitance of CeO2 Nanostructures: Electrochemical and Molecular Dynamics Studies. (9th August 2018) - Jeyaranjan, Aadithya; Sakthivel, Tamil Selvan; Molinari, Marco; Sayle, Dean C.; Seal, Sudipta
Abstract: Nano cerium oxide (CeO2 ) is a promising supercapacitor material, but the effect of morphology on charge storage capacity remains elusive. To determine this effect, three different morphologies, nanorods, cubes, and particles are synthesized by a one‐step hydrothermal process. Electrochemical evaluation through cyclic voltammetry and galvanostatic charge–discharge techniques reveals specific capacitance to be strongly dependent on the nanostructure morphology. The highest specific capacitance in nanorods (162.47 F g −1 ) is due to the substantially larger surface area relative to the other two morphologies and the predominant exposure of the highly reactive {110} and {100} planes. At comparable surface areas, exposed crystal planes exhibit a profound effect on charge storage. The exposure of highly reactive {100} planes in nanocubes induce a greater specific capacitance compared to nanoparticles, which are dominated by the less reactive {111} facets. The experimental findings are supported by reactivity maps of the nanostructures generated by molecular dynamics simulations. This study indicates that supercapacitors with higher charge storage can be designed through a nanostructure morphology selection strategy. Abstract : Morphology and crystal plane‐dependent supercapacitance of CeO2 nanostructures is explored using electrochemical experiments and molecular dynamics simulations. The exposed crystals planes play a crucial role in supercapacitor performance and rate capability of CeO2 nanostructures. Understanding the fundamental effect of exposed crystal planes on charge storage helps designing nanomaterials with superior supercapacitor performance.